2012
DOI: 10.1158/0008-5472.can-11-3290
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor Alpha Mediates Progestin-Induced Mammary Tumor Growth by Interacting with Progesterone Receptors at the Cyclin D1/MYC Promoters

Abstract: Synthetic progesterone used in contraception drugs (progestins) can promote breast cancer growth, but the mechanisms involved are unknown. Moreover, it remains unclear whether cytoplasmic interactions between the progesterone receptor (PR) and estrogen receptor alpha (ERa) are required for PR activation. In this study, we used a murine progestin-dependent tumor to investigate the role of ERa in progestin-induced tumor cell proliferation. We found that treatment with the progestin medroxyprogesterone acetate (M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
85
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 47 publications
7
85
1
2
Order By: Relevance
“…In an MPA-dependent murine mammary tumor model, inhibition of ER with fulvestrant inhibited PR-dependent tumor formation. Guilianeli and his colleagues confirmed earlier studies that ER and PR interact and colocalize (Migliaccio et al 1998, Giulianelli et al 2012, but extended ER/PR cross talk studies with regard to the regulation of gene expression in human breast cancer cell lines and mouse tumors. Both receptors were detected (via ChIP assays) at the promoters of CCND1 and MYC genes in T47D cells.…”
Section: Pr Signaling Cross Talk Is Relevant To Er+ Luminal Breast Casupporting
confidence: 60%
See 2 more Smart Citations
“…In an MPA-dependent murine mammary tumor model, inhibition of ER with fulvestrant inhibited PR-dependent tumor formation. Guilianeli and his colleagues confirmed earlier studies that ER and PR interact and colocalize (Migliaccio et al 1998, Giulianelli et al 2012, but extended ER/PR cross talk studies with regard to the regulation of gene expression in human breast cancer cell lines and mouse tumors. Both receptors were detected (via ChIP assays) at the promoters of CCND1 and MYC genes in T47D cells.…”
Section: Pr Signaling Cross Talk Is Relevant To Er+ Luminal Breast Casupporting
confidence: 60%
“…Significantly, ER and PR interact in both rapid signaling (Razandi et al 2003, Boonyaratanakornkit et al 2007) and transcriptional contexts (Ballare et al 2003, Giulianelli et al 2012, Daniel et al 2015, Mohammed et al 2015. Indeed, cross talk between ER and PR appears to be extensive (Migliaccio et al 1998) and clearly impacts global gene expression and breast cancer cell fate (Giulianelli et al 2012, Daniel et al 2015, Mohammed et al 2015, Need et al 2015 (further discussed later). For example, classic studies demonstrated that in the presence of progestin, ER augments PR-dependent gene expression and tumor growth.…”
Section: Pr Signaling Cross Talk Is Relevant To Er+ Luminal Breast Camentioning
confidence: 94%
See 1 more Smart Citation
“…Hormonally ablated mice and rats differ from endocrine-intact animals, which might more closely reflect the patients analyzed in the present study. Hormone signaling is extremely context-dependent, and there is increasing evidence for interactions between ER and PR at the molecular level that may account for this phenomenon (39).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there appears to be an autoregulatory negative feedback loop between ATBF1 and estrogen-ER signaling, as the transcription of ATBF1 is increased by estrogen-ER while ATBF1 protein is degraded by the estrogen-responsive ubiquitin E3 ligase EFP [15,16]. PR is a well known target gene of estrogen-ER signaling [17], and ERa mediates progestin-induced tumor growth by interacting with PR [18]. We therefore examined whether ATBF1 is also involved in the function of Pg-PR signaling in mammary epithelial cells.…”
Section: Introductionmentioning
confidence: 99%